Developing an ELT- Oriented Online PBL Model to Support EFL Students’ Speaking Fluency - Irma Dewi Isda Isda; Nur Hidayanto Pancoro Setyo Putro; Ari Purnawan Purnawan; Purwati Purwati; Rahmiati Rahmiati (JL3T (Journal of Linguistics, Literature and Language Teaching), 2025)
Project based Learning models need to be developed in English learning. This research is needed to support learning model innovation. The purpose of this study is to produce an online-based PJBL model that is valid and appropriate to use in learning English. This study uses research and development (R&D) methods, with a 4-D development model (Define, Design, Development, Disseminate). However, caused of the time limitation to accomplish the steps, this research only implemented at three steps; define, design and development. The instruments used are interview guidelines, questionnaire sheets, and documentation. The subjects in this study were English teachers at SMA Muhammadiyah Langsa and expert lecturers at Samudra University. The results showed that at the Define stage the development of an Online-based PJBL model in English lessons in senior high schools was needed. At the design stage, a draft model and a hypothetical model are obtained. Furthermore, at the Development stage, the results of the media expert validation analysis with an average of 91.25% while material expert validation analysis with an average of 90% concluded that the draft model developed was valid with a fairly high category. , the percentage of the feasibility of the model based on the teacher's response was 0,83% with the Very Eligible category. Therefore, the Online-based PJBL model is valid and appropriate to use in learning English at SMA Muhammadiyah Langsa.